2016
DOI: 10.17557/tjfc.15482
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF MALE INBRED LINES OF SUNFLOWER (Helianthus annuus L.) FOR RESISTANCE TO DROUGHT VIA CHLOROPHYLL FLUORESCENCE

Abstract: Sunflower (Helianthus annuus L.) suffers from terminal drought accompanying with high temperature stress since it grows mainly in rain fed areas. Therefore, plant breeders try to improve more drought tolerant varieties and to screen their genetic materials for drought resistance. The present study was conducted to determine drought tolerance levels of sunflower male inbred lines developed by Trakya Agricultural Research Institute (TARI), Edirne, Turkey. Inbred lines grown under controlled environmental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, this is the reason why four factors for B are given in formulae. DFI is a reliable indicator used for evaluating and categorizing the drought tolerance of many plants, as well as sunflower (Boureima et al 2012;Kaya et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this is the reason why four factors for B are given in formulae. DFI is a reliable indicator used for evaluating and categorizing the drought tolerance of many plants, as well as sunflower (Boureima et al 2012;Kaya et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This study was a part of National Sunflower Hybrid Breeding Project carried out by Trakya Agriculture Research Institute (TARI, Republic of Turkey Ministry of Food, Agriculture and Livestock), which is the only local supplier of the Turkey's sunflower. Firstly, fifty main and restorer lines were tested under drought conditions and drought-tolerant lines were determined (Pekcan et al 2015;Kaya et al 2016). Later, test hybrids were developed from drought-tolerant parent lines in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The damage to PSII was caused by the formation of reactive oxygen species, which can lead to membrane damage and deterioration of membrane integrity (Nishiyama et al 2006). Chl a fluorescence (ChlF) measurements have been widely used to detect response of photosynthetic apparatus under stress conditions in wide range of species due to its simple, reliable, nondestructive, and rapid testing technique (Boureima et al 2012(Boureima et al , Çiçek et al 2015(Boureima et al , 2018Kaya et al 2016, Umar et al 2019. ChlF measurements allow determining the physiological status of plants based on the detection of changes in PSII components, electron transport chain, and light-dependent photochemical reactions (Lotfi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The JIP-test was potentially valuable tool for estimating the effects of drought on photosynthetic electron transport (Goltsev et al 2012). Numerous studies have shown that determination of the photosynthetic activity was very informative to find out the drought tolerance of plants (Oukarroum et al 2007, Saglam et al 2011, Boureima et al 2012, Ceppi et al 2012, Goltsev et al 2012Çiçek et al 2015Çiçek et al , Kalaji et al 2016Çiçek et al , 2018aKaya et al 2016, Falqueto et al 2017, Semerci et al 2017, Stirbet et al 2018, Khatri and Rathore 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation